Mongo2SPARQL: Automatic and Semantic Query Conversion of MongoDB Query Language to SPARQL - Soussi, Nassima; Boumlik, Abdeljalil; Bahaj, Mohamed (Transactions on Engineering and Computing Sciences, 2017)
In the last decades, the web has experienced a quantitative explosion of digital data handled by companies or organizations, prompting web users to switch to NoSQL system dedicated to Big Data in order to support large web sites destined for a very big audience due to the scalability and high availability of this system. In the other hand, the semantic web technologies has emerged with their considerable performance in data management by giving the web information a well-defined meaning, and allowing machines to intelligently access to different data sources. However, there is no bridge or an open extension toward these two systems in order to facilitate the interconnection between them; in addition, each NoSQL database has its own query language and does not support the standards of other systems (such as semantic web). All these reasons have motivated us to operate in this topic in order to unify the NoSQL query language and contribute in the interoperability of the both world with a specific focus on MongoDB as a NoSQL document oriented database by proposing the first provably semantic preserving algorithm named Mongo2SPARQL which transform MongoDB query language queries to its equivalent SPARQL ones taking into account key/value pairs having value’s type array and embedded document, generating lists/bags and blank nodes after their transformation.